Improving business sustainability at a fast-moving consumer goods company - Mattheus, Pieter (University of the Free State, 2024)
The impact of environmental changes, technological advancements and ever-changing consumer demands form the contextual foundation of the study and underline the significance for companies within the Fast-Moving Consumer Goods (FMCG) industry to streamline operational efficiencies constantly. The primary research objective was to establish how change management can facilitate company sustainability through the high adaptation of digital solutions at an FMCG company. A comprehensive literature study was done to understand Industry 4.0 impact and FMCG industry trends and the change management principles that can facilitate company sustainability by overcoming the challenges when implementing digital systems. A qualitative research method was followed for this study with a sample size of 12 employees, skilled employees (SE) and manager employees (ME), from four business units at Company A, with first-hand experience of the challenges the current paper-based proof of delivery (POD) process delivers. Interviews, written feedback and rich pictures were used for the thematic analysis approach connecting the visual world and the spoken word allowing for a deep understanding of the current POD process (high touchpoint, and paper intense), highlighting the inefficiencies (delays, time, Order-to-Cash impact, frustration) and potential solutions to close the process gaps. Thematic coding highlighted robots, laser guided vehicles (LGV), automation, integrated reporting solutions, and a change in communication as visible current trends of Industry 4.0 within the FMCG industry, validating that the digital developments are aligned with global industry trends. Risk considerations to mitigate potential resistance during digital change rollout, include a phased rollout approach with transparent communication, ensuring sufficient support structures and effective training interventions. The novel systematic approach followed in this research study harnesses the power of rich picture drawings amplifying how this simple visual method can be exploited to capture and understand complex business processes and systems. In the highly demanding consumer-driven environment, the value this approach offers an FMCG company (on a digital transformation journey as part of a long-term sustainability focus), emanates from the ease it can be incorporated into a company’s problem-solving ‘toolkit’, at the same time help create urgency by facilitating self-generated employee insights and ideas (reducing resistance to new digital change). As the first point of contact during periods of change, the research findings include manager development and upskilling as a crucial strategic focus area to ensure future readiness. Training offerings must empower employees for the digital future and have the flexibility to be tailored to individual needs. To be a future-fit FMCG company, the research findings show the need for an integrated digital ecosystem approach that provides uninterrupted communication to ensure real-time visibility of product movement to all stakeholders involved. Finally, this research study highlights the potential loopholes and inherent inefficiencies paper-based processes possess, bringing home the importance of actively identifying and reducing paper-based processes.
Keywords: FMCG; Digital transformation; Change management; Communication; Rich picture